Hubungan Kebiasaan Penggunaan Peralatan Bersama dengan Kejadian Pediculosis Capitis Pada Santri di Pondok Pesantren - Rajagukguk, Marlina (Universitas Pahlawan Tuanku Tambusai, 2024)
The incidence of Pediculosis capitis causes significant morbidity, such as psychosocial disorders, reduced sleep quality and impaired learning concentration so that there can be a decrease in learning achievement. This study aims to determine the relationship between the habit of using shared equipment and the incidence of Pediculosis capitis in students at the Usamah Bin Zaid Islamic Boarding School, Kec. Confusion. This research is an analytical research with quantitative methods and uses a cross sectional design. The population in this study were students at the Usamah Bin Zaid Islamic Boarding School, totaling 120 people. The sample size was 54 people obtained using stratified random sampling technique. Data analysis used univariate and bivariate data analysis with the Chi Sqaure test. The results of the study showed that the habit of using equipment was mostly in the category of borrowing equipment, as many as 28 people (77.8%). Pediculosis capitis was in the positive category as many as 32 people (59.3%). There is a relationship between the habit of using equipment and the incidence of Pediculosis capitis (p = 0.000). And there is no relationship between hair condition and the incidence of Pediculosis capitis (p = 0.506). The dominant variable associated with the incidence of Pediculosis capitis is borrowing equipment and using it together.